Terahertz plasmon and surface-plasmon modes in cylindrical metallic nanowires - 吴平 徐文 李龙龙 占铁城 吴卫东 (Chinese physics B, 2014)
We present a theoretical study on collective excitation modes associated with plasmon and surface-plasmon oscilla- tions in cylindrical metallic nanowires. Based on a two-subband model, the dynamical dielectric function matrix is derived under the random-phase approximation. An optic-like branch and an acoustic-like branch, which are free of Landau damp- ing, are observed for both plasmon and surface-plasmon modes. Interestingly, for surface-plasmon modes, we find that two branches of the dispersion relation curves converge at a wavevector qz = qrnax beyond which no surface-plasmon mode exists. Moreover, we examine the dependence of these excitation modes on sample parameters such as the radius of the nanowires. It is found that in metallic nanowires realized by state-of-the-art nanotechnology the intra- and inter-subband plasmon and surface-plasmon frequencies are in the terahertz bandwidth. The frequency of the optic-like modes decreases with increasing radius of the nanowires, whereas that of the acoustic-like modes is not sensitive to the variation of the radius. This study is pertinent to the application of metallic nanowires as frequency-tunable terahertz plasmonic devices.